Cardiac Regeneration: Lessons From Development. Issue 6 (17th March 2017) - Galdos, Francisco X.; Guo, Yuxuan; Paige, Sharon L.; VanDusen, Nathan J.; Wu, Sean M.; Pu, William T.
Abstract : Palliative surgery for congenital heart disease has allowed patients with previously lethal heart malformations to survive and, in most cases, to thrive. However, these procedures often place pressure and volume loads on the heart, and over time, these chronic loads can cause heart failure. Current therapeutic options for initial surgery and chronic heart failure that results from failed palliation are limited, in part, by the mammalian heart's low inherent capacity to form new cardiomyocytes. Surmounting the heart regeneration barrier would transform the treatment of congenital, as well as acquired, heart disease and likewise would enable development of personalized, in vitro cardiac disease models. Although these remain distant goals, studies of heart development are illuminating the path forward and suggest unique opportunities for heart regeneration, particularly in fetal and neonatal periods. Here, we review major lessons from heart development that inform current and future studies directed at enhancing cardiac regeneration.